Experience with free fibula transfer with screw fixation as a primary modality of treatment for congenital pseudarthosis of tibia in children - Series of 26 cases - Guru Dayal Singh Kalra; Amit Agarwal (Indian Journal of Plastic Surgery)
Background: Congenital pseudarthrosis is one of the greatest challenges of paediatric orthopaedic practice. Treatment options and literature addressing this condition are numerous, reflecting the difficulty in management. We aimed to study the effectiveness of free fibula transfer as a primary modality of treatment in children with this condition in terms of achieving length, union, and normal axis of the involved leg. Materials and Methods: During the period of 2001 to 2010, 26 children with congenital pseudarthrosis of tibia between age group of 2-8 years were evaluated and were reconstructed using contra-lateral free fibula graft, and then patients were followed up for 5 years subsequently. Patients were examined and time of bony union, weight bearing ability and walking without support were noted. Any complication directly or indirectly related to surgery with any complication seen in the due course of follow up of 5 years was also taken care of. Results: In our experience with treatment of congenital pseudarthrosis over a span of 10 years with free fibula transfer, the results have been gratifying with no flap loss. All our patients had UNEVENTFUL post-op recovery. Only 2 patients out of 26 had non-union, for which cancellous bone grafting was done (7.6%). Most of the patients were ambulatory with support by 3-6 months and continued to walk without support after a span of 18-24 months. The incidence of stress fracture in our study over the follow-up period was 4 out of 26 pts (15.3%). None of them had any deformity in the donor leg. Conclusion: When compared to other surgical modalities of treatment of the problem in question, vascularised free fibula transfer has emerged as a real saviour with good patient compliance and less complication rate in our study. It achieves the desired target with no residual deformities and near normal to normal gait with no stigma of bone removal from other leg.